Dephasing and diffusion on the alveolar surface - Buschle, Lukas R.; Kurz, Felix T.; Wagner, Willi Linus; Dürr, Julia; Stiller, Wolfram; Konietzke, Philip; Wünnemann, Felix; Mall, Marcus A.; Wielpütz, Mark Oliver; Ziener, Christian H. (Physical review, 2017)
We propose a surface model of spin dephasing in lung tissue that includes both susceptibility and diffusion effects to provide a closed-form solution of the Bloch-Torrey equation on the alveolar surface. The nonlocal susceptibility effects of the model are validated against numerical simulations of spin dephasing in a realistic lung tissue geometry acquired from synchotron-based μCT data sets of mouse lung tissue, and against simulations in the well-known Wigner-Seitz model geometry. The free induction decay is obtained in dependence on microscopic tissue parameters and agrees very well with in vivo lung measurements at 1.5 Tesla to allow a quantification of the local mean alveolar radius. Our results are therefore potentially relevant for the clinical diagnosis and therapy of pulmonary diseases.